2015
DOI: 10.1371/journal.pone.0141817
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Frequency of CD14+CD169+ Monocytes/Macrophages in Patients with Colorectal Cancer

Abstract: ObjectiveMonocytes and macrophages can infiltrate into tumor microenvironment and regulate the progression of tumors. This study aimed at determining the frequency of different subsets of circulating monocytes and tumor infiltrating macrophages (TIMs) in patients with colorectal cancer (CRC).MethodsThe frequency of different subsets of circulating monocytes was characterized in 46 CRC patients and 22 healthy controls (HC) by flow cytometry. The frequency of different subsets of macrophages was analyzed in TIMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
(56 reference statements)
2
18
0
Order By: Relevance
“…In homeostatic conditions, SIGLEC1 + macrophages are mainly in the bone marrow, liver, spleen, colon, and lymph node, and they are involved in erythropoiesis and adaptive immune responses ( Chávez-Galán et al., 2015 ). Consistent with our findings, SIGLEC1 + macrophages have been identified in colorectal ( Li et al., 2015 ) and hepatocellular carcinoma ( Zhang et al., 2016 ). Infiltration of SIGLEC1 + macrophages in colorectal cancer was associated with tumor progression, but in hepatocellular carcinoma they predicted favorable patient outcomes ( Zhang et al., 2016 ), underpinning the hypothesis that TAM phenotypes/activation are organ and cancer specific.…”
Section: Discussionsupporting
confidence: 92%
“…In homeostatic conditions, SIGLEC1 + macrophages are mainly in the bone marrow, liver, spleen, colon, and lymph node, and they are involved in erythropoiesis and adaptive immune responses ( Chávez-Galán et al., 2015 ). Consistent with our findings, SIGLEC1 + macrophages have been identified in colorectal ( Li et al., 2015 ) and hepatocellular carcinoma ( Zhang et al., 2016 ). Infiltration of SIGLEC1 + macrophages in colorectal cancer was associated with tumor progression, but in hepatocellular carcinoma they predicted favorable patient outcomes ( Zhang et al., 2016 ), underpinning the hypothesis that TAM phenotypes/activation are organ and cancer specific.…”
Section: Discussionsupporting
confidence: 92%
“…These different functions of TAMs are sometimes referred to as M1 macrophages (anti-tumorigenic) or M2 macrophages (pro-tumorigenic), although their polarization status is much more complex due to a high degree of plasticity [ 65 ]. Few studies have demonstrated that presence of TAMs and their subtype distribution in primary tumors are associated with clinical outcome of CRC patients [ 66 , 67 , 68 ]. It was found that both TAM subsets, M1 and M2, were found to be present at increased levels in primary tumors [ 68 ].…”
Section: Tumor-immune System Interactions In Crcmentioning
confidence: 99%
“…Few studies have demonstrated that presence of TAMs and their subtype distribution in primary tumors are associated with clinical outcome of CRC patients [ 66 , 67 , 68 ]. It was found that both TAM subsets, M1 and M2, were found to be present at increased levels in primary tumors [ 68 ]. Presence of M1 macrophages has been correlated with better clinical outcome [ 66 ], whereas expression of M2 macrophage markers has been correlated with worse clinical outcome in CRC [ 67 ].…”
Section: Tumor-immune System Interactions In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies suggested that M2-like TAMs in breast cancer tissue could migrate into peripheral blood to become circulating M2-like monocytes and facilitate breast tumor metastasis 15 - 17 . Furthermore, circulating M2-like monocytes are elevated in some cancers, such as lung cancer 18 , colorectal cancer 19 , and classical Hodgkin Lymphoma 20 . Therefore, circulating M2-like monocytes may serve as a new tumor biomarker for breast cancer.…”
Section: Introductionmentioning
confidence: 99%